11α hydroxylation of 16α, 17‐epoxyprogesterone in biphasic ionic liquid/water system by Aspergillus ochraceus. Issue 2 (16th May 2012) - Mao, Shuhong; Hua, Boyuan; Wang, Na; HU, Xiaojie; Ge, Zhijiang; Li, Yanqing; Liu, Sha; Lu, Fuping
Abstract BACKGROUND: The improved efficiency of steroid biotransformation using the biphasic system is generally attributed to the positive effect on the solubility of substrate in aqueous media. A promising alternative for the application of organic solvents in biphasic systems is the use of ionic liquids (ILs). This study aims to investigate the applicability of the biphasic ILs/water system for 11α hydroxylation of 16α, 17‐epoxyprogesterone (HEP) by Aspergillus ochraceus. RESULTS: Of the seven ILs tested, [C3mim][PF6] exhibited the best biocompatibility, with markedly improved biotransformation efficiency. In the [C3mim][PF6]‐based biphasic system, substrate conversion reached 90% under the condition in which buffer pH, volume ratio of buffer to ILs, cell concentration, and substrate concentration were 4.8, 10/1, 165 g L−1 and 20 g L−1, respectively. This is more efficient than that of the monophasic aqueous system. The effects of the cations and anions of these ILs on the 11α hydroxylation of 16α, 17‐epoxyprogesterone (HEP) by A. ochraceus is also discussed. CONCLUSION: The above results showed that IL/water biphasic system improved the efficiency of 11α hydroxylation of 16α, 17‐epoxyprogesterone (HEP) by A. ochraceus, thus suggesting the potential industrial application of ILs‐based biphasic systems for steroid biotransformation. © 2012 Society of Chemical Industry